(untitled) - PD Dr. Tanja Hitzel-Cassagnes; Dr. Samira Akbarian; Prof. Dr. Cengiz Barskanmaz, LL.M.; Prof. Dr. Boris Burghardt; Dr. Klaas Hendrik Eller; Prof. Dr. Aziz Epik, LL.M. (Cambridge); Prof. Dr. Isabel Feichtner, LL.M. (Cardozo Law School); Prof. Dr. Felix Hanschmann; Dr. Johan Horst, LL.M. (Georgetown); Prof. Dr. Eva Kocher; Prof. Dr. Nora Markard, MA (King’s College London); PD Dr. Kolja Möller; et al. (KJ Kritische Justiz, 2023)
Kritische Justiz analyses the law and its implementation in view of the prevailing social background and breaches the conventional approach to legal questions by detaching it from its economic and political context. The journal contains articles, reports, commentaries and documentations on all important juridical fields and publishes crucial judicial decisions on social matters. Kritische Justiz addresses lawyers, law students, legal scholars, social scientists, unionists, social workers, teachers, economists, and environmental scientists. Website: www.kj.nomos.de